# Solve the following equations:

(a) 10p = 100 (b) 10p + 10 = 100 (c) p/4 = 5

(d) −p/3 = 5 (e) 3p/4 = 6 (f) 3s = –9

(g) 3s + 12 = 0 (h) 3s = 0 (i) 2q = 6

(j) 2q – 6 = 0 (k) 2q + 6 = 0 (l) 2q + 6 = 12

**Solution:**

We use the basic concepts of simple linear equations to solve the questions given.

(a) 10 p = 100

Dividing both the sides by 10 we get,

10p/10 = 100/10

p = 10

(b) 10p + 10 =100

Subtracting 10 from both sides we get,

10p + 10 − 10 = 100 −10

10p = 90

Dividing both the sides by 10 we get,

10p/10 = 90/10

p = 9

(c) p/4 = 5

Multiplying both the sides by 4 we get,

(p/4) × 4 = 5 × 4

p = 20

(d) −p/3 = 5

Multiplying both the sides by -3 ,

(−p/3) × (-3) = 5 × (-3)

p = -15

(e) 3p/4 = 6

Multiplying both the sides by 4, we get

(3p/4) × 4 = 6 × 4

3p = 24

Dividing both the sides by 3 we get,

3/3p = 24/3

p = 8

(f) 3s = -9

Dividing both the sides by 3,

3s/3 = -9/3

s = -3

(g) 3s + 12 = 0

Subtracting 12 from both the sides of the equation we get,

3s + 12 - 12 = 0 - 12

3s = -12

Dividing both the sides by 3 we get,

3s/3 = -12/3

s = -4

(h) 3s = 0

Dividing both the sides by 3 we get,

3/3 s = 0/3

s = 0

(i) 2q = 6

Dividing both the sides by 2 we get,

2q/2 = 6/2

q = 3

(j) 2q - 6 = 0

Adding 6 to both sides of the equation we get,

2 q - 6 + 6 = 0 + 6

2 q = 6

Dividing both the sides by 2 we get,

2q/2 = 6/2

q = 3

(k) 2q + 6 = 0

Subtracting 6 from both the sides of the equation we get,

2q + 6 − 6 = 0 - 6

2q = -6

Dividing both the sides by 2 we get,

2q/2 = -6/2

q = -3

(l) 2q + 6 =12

Subtracting 6 from both the sides of the equation we get,

2q + 6 − 6 = 12 - 6

2q = 6

Dividing both the sides by 2 we get,

2q/2 = 6/2

q = 3

**Video Solution:**

## Solve the following equations: (a) 10p = 100 (b) 10p + 10 = 100 (c) p/4 = 5 (d) −p/3 = 5 (e) 3p/4 = 6 (f) 3s = –9 (g) 3s + 12 = 0 (h) 3s = 0 (i) 2q = 6 (j) 2q – 6 = 0 (k) 2q + 6 = 0 (l) 2q + 6 = 12

### NCERT Solutions for Class 7 Maths - Chapter 4 Exercise 4.2 Question 4

Solve the following equations: (a) 10p = 100 (b) 10p + 10 = 100 (c) p/4 = 5 (d) −p/3 = 5 (e) 3p/4 = 6 (f) 3s = –9 (g) 3s + 12 = 0 (h) 3s = 0 (i) 2q = 6 (j) 2q – 6 = 0 (k) 2q + 6 = 0 (l) 2q + 6 = 12

(a) p = 10 ,(b) p = 9, (c) p = 20, (d) p = −15 , (e) p = 8 , (f) s = -3, (g) s = -4, (h) s = 0 , (i) q = 3 , (j) q = 3 , (k) q = -3, (l) q = 3